Succession Planning at HEIs: Leadership Style, Career Development and Knowledge Management Practices as Its Predictors - Ishak, Awanis Ku; Kamil, Bidayatul Akmal Mustafa (International Review of Management and Marketing, 2016)
Succession planning has spelt many affirmative returns to organizations, several reviews have indicated that this corporate initiative lacks in its planning, implementing and managing. It happens at HEIs in Malaysia that have been slow to embrace corporate formal succession planning approach. Perhaps the appropriate leadership style, perception of career development opportunities as well as knowledge management practices may enhance the succession planning of public universities in Malaysia. Therefore this study specifically intends to examine the significant relationships between succession planning and its predictors which are leadership style, career development and knowledge management practices. The sampling frame in this study contained a list of all administrative officers from grade N41 to grade N54 at 19 public universities staff. According to the results, there is significant influence of two independent variables which are leadership style and knowledge management on successive planning effectiveness. Nevertheless, career management does not influence successive planning effectiveness although both are significantly related. Keywords: Leadership, Knowledge and Management Practice JEL Classifications: M1, M5